Characterization of Peripheral Activity States and Cortical Local Field Potentials of Mice in an Elevated Plus Maze Test - Okonogi, Toya; Nakayama, Ryota; Sasaki, Takuya; Ikegaya, Yuji (Frontiers in Behavioral Neuroscience, 2018)
Elevated plus maze (EPM) tests have been used to assess animal anxiety levels. Little information is known regarding how physiological activity patterns of the brain-body system are altered during EPM tests. Herein, we monitored cortical local field potentials, electrocardiograms, electromyograms, and respiratory signals in individual mice that were repeatedly exposed to EPM tests. On average, mouse heart rates were higher in open arms. In closed arms, the mice occasionally showed decreased heart and respiratory rates lasting for several seconds or minutes, characterized as low-peripheral activity states of peripheral signals. The low-activity states were observed only when the animals were in closed arms, and the frequencies of the states increased as the testing days proceeded. During the low-activity states, the delta and theta powers of cortical local field potentials were significantly increased and decreased, respectively. These results demonstrate that cortical oscillations crucially depend on whether an animal exhibits low-activity states in peripheral organs rather than the EPM arm in which the animal is located. These results suggest that combining behavioral tests with physiological makers enables a more accurate evaluation of rodent mental states.